O perfil de uma escola pública de Humaitá-AM: uma análise do desempenho do SAEB e a relação com as práticas pedagógicas - (:unkn) unknown (Universidade Federal do Amazonas, 2022)
Faced with the concern with the performance of elementary schools I, in the municipality of Humaitá-AM, we sought to understand the relationship between pedagogical practices carried out within the walls of the school, with the performance presented in standardized external evaluations, more specifically the evaluation of the Basic Education Assessment System - SAEB, some directive questions were formulated with the objective of analyzing influences of pedagogical practices developed in the context of a public school with better performance in SAEB (2019). In the discourse of the teaching and managerial staff, the pedagogical practices developed by the teams, manager and teacher of the school to overcome the goals established by the SAEB are probed, and how much has facilitated the teaching and learning of the subject (student) in training. The approach of this study is qualitative, the method used will be descriptive research, the production of data will be carried out from the semi-structured interview with teachers from the 1st to 5th grades of elementary school and the school management team. For the systematization and analysis of the data generated from the instrument, the technique of content analysis was adopted, in view of the need for a more in-depth view of the reality of the environment where the school is located. As final considerations of our research, we point out that the realization of pedagogical practices is configured in a social action from human intervention, that said, we highlight its constant, unfinished and in some cases contradictory construction process. Therefore, what we reaffirm is that in the daily life of the Edmee Monteiro Brasil Municipal School, managerial and teaching practices are carried out, among which there are those that corroborate the global learning of the learner as an active subject in the construction of his knowledge, but practices were also identified. totally directed to training for the accomplishment of external evaluations, in this case the SAEB, and even literacy practices that do not contemplate, nor consider the student as a protagonist in the process.
Keywords: Avaliação educacional - Brasil; Ensino fundamental - Avaliação; Prática de ensino; CIENCIAS HUMANAS; Práticas pedagógicas; Práticas de gestão; Avaliação externa; SAEB